Effect of Prickly Pear Cactus Peel Supplementation on Milk Production, Nutrient Digestibility and Rumen Fermentation of Sheep and the Maternal Effects on Growth and Physiological Performance of Suckling Offspring - Sabrin A. Morshedy; Aymen E. Abdal Mohsen; Mohamed M. Basyony; Rafa Almeer; Mohamed M. Abdel-Daim; Yassmine M. El-Gindy (Animals, 2020)
Prickly pear cactus peels (Opuntia ficus-indica, PPCP) are sustainable byproducts available in arid regions and a rich source of antioxidants. Fifteen multiparous Barki ewes (2–3 years old, 46.94 ± 0.59 kg body weight, BW) at postpartum were individually distributed in three equal groups and fed diets supplemented with PPCP at doses of 0, 5 and 10 g/head/day. Lambs were individually distributed into three equal groups according to their mothers’ groups to investigate the maternal effect on lambs’ growth performance, hematology and serum metabolites. This trial lasted for 56 days from birth to weaning. Moreover, nine adult male Barki sheep with a live BW of 65.76 ± 0.54 kg were randomly allocated into three equal groups to determine the effect of PPCP on the nutrient digestibility of the experimental diets. The results indicate that supplementing PPCP at low levels (5 g/head/day) increased milk yield (p = 0.050), fat-corrected milk (p = 0.022), energy-corrected milk (p = 0.015) and the yield of milk constituents compared to 10 g PPCP and the control group. In addition, lambs suckling from ewes fed the diet supplemented with 5 g PPCP had a higher (p = 0.001) weaning BW compared to other groups. Serum total protein, globulin, superoxide dismutase, glutathione peroxidase enzyme activities and the triiodothyronine hormone improved significantly in lambs suckling from ewes fed diets supplemented with 5 g PPCP compared to the control group. Serum cholesterol profile and kidney activities were enhanced significantly in lambs suckling from ewes fed diets supplemented with 5 and 10 g of PPCP compared to the control group. The dietary supplementation of 5 g PPCP improved the crude protein digestibility, digestible crude protein value, nitrogen balance and rumen fermentation characteristics of male sheep compared to the control group. In conclusion, supplementation with 5 g PPCP improved ewes’ milk production, offspring growth and physiological status. Furthermore, it improved the crude protein digestibility and rumen fermentation characteristics of Barki sheep.